2011
DOI: 10.1007/978-1-4614-0106-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Innate-Adaptive Crosstalk: How Dendritic Cells Shape Immune Responses in the CNS

Abstract: Dendritic cells (DCs) are a heterogeneous group of professional antigen presenting cells that lie in a nexus between innate and adaptive immunity because they recognize and respond to danger signals and subsequently initiate and regulate effector T-cell responses. Initially thought to be absent from the CNS, both plasmacytoid and conventional DCs as well as DC precursors have recently been detected in several CNS compartments where they are seemingly poised for responding to injury and pathogens. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 138 publications
0
26
0
Order By: Relevance
“…By contrast, the adaptive immune response develops over a longer time scale, typically peaking between 1 and 3 weeks, depending on the injury or pathogen [69,113]. Adaptive immunity is activated and stimulated by components of the innate immune response, and has been well reviewed elsewhere [114][115][116][117][118]. The adaptive immune response is initiated by antigen presentation using major histocompatibility complex (MHC) II molecules, which are expressed on proinflammatory myeloid cells.…”
Section: Reactive Astrocytes Secrete a Molecular Barriermentioning
confidence: 99%
“…By contrast, the adaptive immune response develops over a longer time scale, typically peaking between 1 and 3 weeks, depending on the injury or pathogen [69,113]. Adaptive immunity is activated and stimulated by components of the innate immune response, and has been well reviewed elsewhere [114][115][116][117][118]. The adaptive immune response is initiated by antigen presentation using major histocompatibility complex (MHC) II molecules, which are expressed on proinflammatory myeloid cells.…”
Section: Reactive Astrocytes Secrete a Molecular Barriermentioning
confidence: 99%
“…Subsequently, CD8+ OVA-specific T cells accumulate in the cervical lymph nodes and thereafter in the CNS (Ling et al 2003). Upon intracerebral injection, mature OVA-loaded DC migrate from the CNS to cervical lymph nodes to prime OVA-specific T-cell responses (Karman et al 2004) reviewed by (Clarkson et al 2012).…”
Section: Multiple Sclerosis and Eaementioning
confidence: 99%
“…Hence, they present an attractive alternative to targeting cell populations hidden behind tissue barriers between the periphery, perivascular spaces, and the brain parenchyma that are difficult to surmount. Excellent recent reviews related to this article are available, dealing with CNS leukocyte traffic, antigen presenting cell subsets of the CNS, and CNS-lymphoid tissue interactions (Clarkson et al 2012;Mohammad et al 2012;Ousman and Kubes 2012;Ransohoff 2012;Prinz et al 2011;Ransohoff and Engelhardt 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DCs, the most effective professional antigen-presenting cells (APC) in vivo, were used to evaluate H9N2 vaccination [6,7]. Previous studies have demonstrated that DCs played an essential role in controlling the innate immune response against influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%